Fabrication and characterization of Fe-based metallic glasses by Selective Laser Melting. (January 2019) - Nong, X.D.; Zhou, X.L.; Ren, Y.X.
Highlights: Fe-based metallic glasses with unrestricted geometry can be fabricated using SLM. The crystalline phases in the gas-atomized powder disappeared after SLM. High quality Fe-based metallic glasses obtained by choosing appropriate parameters. Abstract: Fe-based metallic glasses (MGs) can be potential structural materials owing to an exceptional combination of strength, corrosion and wear resistance properties. However, many traditional methods are difficult to fabricate Fe-based MGs with complex geometry. In this study, a new metallurgical processing technology, selective laser melting (SLM), was employed to fabricate Fe-Cr-Mo-W-Mn-C-Si-B metallic glasses. The microstructure, thermal stability and mechanical properties of the as-fabricate samples processing with different laser energy density have been investigated by X-Ray diffraction (XRD), scanning electron microscope (SEM), transmission electron microscopy (TEM), differential scanning calorimetry (DSC) and nano-hardness. Thanks to the high cooling rates of SLM, the crystalline phases in the gas-atomized powder almost completely disappeared and nearly fully amorphous structure parts were obtained after SLM processing. By choosing appropriate parameters, the size and quantity of the pores were reduced effectively and the relative density of the samples can reach values of over 96%. Although additional work is required to remove the residual porosity and avoid the formation of cracks during processing, the present results contribute to the development of Fe-based bulk metallic glasses parts with complex geometry via the SLM.